2009
DOI: 10.3168/jds.2009-2126
|View full text |Cite
|
Sign up to set email alerts
|

Production of exopolysaccharides by Lactobacillus and Bifidobacterium strains of human origin, and metabolic activity of the producing bacteria in milk

Abstract: This work reports on the physicochemical characterization of 21 exopolysaccharides (EPS) produced by Lactobacillus and Bifidobacterium strains isolated from human intestinal microbiota, as well as the growth and metabolic activity of the EPS-producing strains in milk. The strains belong to the species Lactobacillus casei, Lactobacillus rhamnosus, Lactobacillus plantarum, Lactobacillus vaginalis, Bifidobacterium animalis, Bifidobacterium longum, and Bifidobacterium pseudocatenulatum. The molar mass distribution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
95
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 120 publications
(100 citation statements)
references
References 32 publications
(41 reference statements)
5
95
0
Order By: Relevance
“…This study presents a potentially new EPS isolated from B. longum subsp. longum CRC 002 with a proposed repeating unit composition of 2 galactose : 3 glucose, which is different from other excreted EPS characterized from B. longum (Abbad Andaloussi et al, 1995;Roberts et al, 1995;Salazar et al, 2009) as well as from B. pseudocatenulatum (Salazar et al, 2009). The EPS composition among B. longum subsp.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…This study presents a potentially new EPS isolated from B. longum subsp. longum CRC 002 with a proposed repeating unit composition of 2 galactose : 3 glucose, which is different from other excreted EPS characterized from B. longum (Abbad Andaloussi et al, 1995;Roberts et al, 1995;Salazar et al, 2009) as well as from B. pseudocatenulatum (Salazar et al, 2009). The EPS composition among B. longum subsp.…”
Section: Discussionmentioning
confidence: 78%
“…Only 17 % of lactobacilli and bifidobacterial strains isolated from human gastrointestinal microbiota showed EPS production by phenotypic methods (Ruas-Madiedo et al, 2007). Bifidobacterium longum strain YIT4028 has been reported to have cell wall polysaccharides consisting of rhamnogalactan (Nagaoka et al, 1995), while three out of four EPSs characterized from B. longum also contained rhamnose (Salazar et al, 2009). More recently, the EPS repeating unit from B. longum strain JBL05 was shown to be a heptasaccharide containing glucose, galactose and rhamnose (Kohno et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Hi gh molecular weight of EPS contributed to limiting the susceptibility to syneresis and improving the texture of fermented milk by cross-linking of the EPS into a network structure with the proteins during fermentation [Hassan et . The difference in molecular weights of the EPSs could be attributed to the different producing strains, the culture media, and the growth conditions used [Salazar et al, 2009].…”
Section: Eps Characterizationmentioning
confidence: 99%
“…Li et al [2014c] also reported that soymilk fermented with EPS-producing L. plantarum 70810 had more characteristic flavor compounds and lower beany flavor compounds than those in the original soymilk base. The EPS-producing Lactobacillus strains were not found to produce excessive amount of disgusting flavor compounds when used in fermented milks [Salazar et al, 2009]. Additionally, fermented milk fermented with EPS-producing S. thermophilus 05-34 exhibited significantly higher scores on sensory property than the fermented milk containing non-EPS-producing S. thermophiles 05-32 [Qin et al, 2011].…”
Section: Microbiological and Physicochemical Analyses Of Fermented Milkmentioning
confidence: 99%
See 1 more Smart Citation